Diurnal regulation of metabolism by Gs-alpha in hypothalamic QPLOT neurons. - Kevin D Gaitonde; Mutahar Andrabi; Courtney A Burger; Shane P D'Souza; Shruti Vemaraju; Bala S C Koritala; David F Smith; Richard A Lang (PLoS ONE)
Neurons in the hypothalamic preoptic area (POA) regulate multiple homeostatic processes, including thermoregulation and sleep, by sensing afferent input and modulating sympathetic nervous system output. The POA has an autonomous circadian clock and may also receive circadian signals indirectly from the suprachiasmatic nucleus. We have previously defined a subset of neurons in the POA termed QPLOT neurons that are identified by the expression of molecular markers (Qrfp, Ptger3, LepR, Opn5, Tacr3) that suggest receptivity to multiple stimuli. Because Ptger3, Opn5, and Tacr3 encode G-protein coupled receptors (GPCRs), we hypothesized that elucidating the G-protein signaling in these neurons is essential to understanding the interplay of inputs in the regulation of metabolism. Here, we describe how the stimulatory Gs-alpha subunit (Gnas) in QPLOT neurons regulates metabolism in mice. We analyzed Opn5cre; Gnasfl/fl mice using indirect calorimetry at ambient temperatures of 22°C (a historical standard), 10°C (a cold challenge), and 28°C (thermoneutrality) to assess the ability of QPLOT neurons to regulate metabolism. We observed a marked decrease in nocturnal locomotion of Opn5cre; Gnasfl/fl mice at both 28°C and 22°C, but no overall differences in energy expenditure, respiratory exchange, or food and water consumption. To analyze daily rhythmic patterns of metabolism, we assessed circadian parameters including amplitude, phase, and MESOR. Loss-of-function GNAS in QPLOT neurons resulted in several subtle rhythmic changes in multiple metabolic parameters. We observed that Opn5cre; Gnasfl/fl mice show a higher rhythm-adjusted mean energy expenditure at 22°C and 10°C, and an exaggerated respiratory exchange shift with temperature. At 28°C, Opn5cre; Gnasfl/fl mice have a significant delay in the phase of energy expenditure and respiratory exchange. Rhythmic analysis also showed limited increases in rhythm-adjusted means of food and water intake at 22°C and 28°C. Together, these data advance our understanding of Gαs-signaling in preoptic QPLOT neurons in regulating daily patterns of metabolism.